Description of Neoperla philippinensis sp. nov. confirmed using integrative taxonomy and some notes on Neoperla oculata Banks, 1924 (Plecoptera: Perlidae) - Pelingen, Arthien Lovell (Zootaxa, 2024)
I re-examine the assumed phenotypic variable Neoperla oculata Banks, 1924 (Plecoptera, Perlidae) and describe Neoperla philippinensis sp. nov. All material examined herein are collections from the Mindanao region, of which supplementary information were provided including COI mtDNA accessions, female adult associations, and egg morphology characterization.